Kolaborasi Model Problem Centered Learning (PCL) dan Numbered Head Together (NHT) untuk Meningkatkan Hasil Belajar Siswa Pada Pokok Bahasan Pecahan - Dewi Nur Hasanah Indah; Tri Susilaningtyas; Sholahudin Al Ayubi (FKIP Universitas Islam Jember, 2017)
Learning is a key activity of the educational process. Researchers conducted observations in class VII MTs. SA Nurul Qona’ah Mumbulsari and approximately 46% of the data obtained shows student scores ≤ 70. The type of research used is classroom action research (PTK). Based on the results of research, the percentage of student learning activities in the first cycle of 52,39% and cycle II of 87,72%. While the results of daily test of students on the cycle I obtained an average value of 71,3 while in the second cycle of 76,42. It proves that the result of student learning can be increased by applying type Numbered Head Together (NHT) Collaboration Problem Centered Learning (PCL). Keywords : Problem Centered Learning (PCL), Numbered Head Together (NHT), Learning Outcomes.